Răspuns:
1) Distanța dintre A(0,5) și B(0, -3) este |5 - (-3)| = 8.
2) Distanța dintre A(-4,0) și B(3,0) este |-4 - 3| = 7.
3) Distanța dintre A(1,-2) și B(-1,3) este √[(1 - (-1))^2 + ((-2) - 3)^2] = √[4 + 25] = √29.
4) Distanța dintre A(1,3) și B(2,2) este √[(1 - 2)^2 + (3 - 2)^2] = √[1 + 1] = √2.
5) Distanța dintre A(-3,-4) și B(2,3) este √[(-3 - 2)^2 + ((-4) - 3)^2] = √[25 + 49] = √74.
6) Distanța dintre A(-2,1) și B(1,-4) este √[(-2 - 1)^2 + (1 - (-4))^2] = √[9 + 25] = √34.
7) Distanța dintre A(3,4) și B(3,-6) este |4 - (-6)| = 10.
8) Distanța dintre A(-5,1) și B(6,1) este |-5 - 6| = 11.